Sunward flows in the magnetosheath associated with the magnetic pressure gradient and magnetosheath expansion - Madanian, H.; Pfau-Kempf, Y.; Rice, R.; Liu, T.; Karlsson, T.; Raptis, S.; Turner, D.; Beedle, J. (Frontiers in Astronomy and Space Sciences, 2025)
A density structure within the magnetic cloud of an interplanetary coronal mass ejection impacted Earth and caused significant perturbations in plasma boundaries. Using spacecraft data, we describe the effects of this structure on the magnetosheath plasma downstream of the bow shock. During this event, the bow shock breathing motion is evident due to changes in the upstream dynamic pressure. A magnetic enhancement forms in the inner magnetosheath and ahead of a plasma compression region. The structure exhibits characteristics of a fast magnetosonic shock wave, propagating earthward and perpendicular to the background magnetic field and further accelerating the already heated magnetosheath plasma. Following these events, a sunward motion of the magnetosheath plasma is observed. Ion distributions show that both the high-density core population and the high-energy tail of the distribution of the distribution propagate sunward, indicating that the sunward flows are caused by magnetic field line expansion in the very low β magnetosheath plasma. Rarefaction effects and enhancement of the magnetic pressure in the magnetosheath result in magnetic pressure gradient forcing, which drives the expansion of magnetosheath magnetic field lines. This picture is supported by a reasonable agreement between the estimated plasma accelerations and the magnetic pressure gradient force.